Prospects for improving the color fastness of thermally modified wood - TSAPKO, Yuriy; TSAPKO, Alexey; BONDARENKO, Olga; LIALINA, Natalya; KAVERIN, Kostyantin; YUSHCHENKO, Alina (Ways to Improve Construction Efficiency, 2025)
It is proved that the color of wood tends to darken due to changes in the chemical components of wood, such as the degradation of amorphous carbohydrates during heat treatment at high temperature. Exposure of wood to high temperatures for a certain period of time improves not only its dimensional stability and durability, but also gives it an attractive dark color. The use of heat treatment has significantly changed the values of the color parameters L*, a*, b* in the samples of thermally modified wood. The L* parameter on the end and stratum surfaces was significantly higher (72 for the end surface and 80 for the stratum) in the control samples. As a result of the heat treatment, the L* value decreased significantly at 160 °C, with a treatment duration of 10 hours, to 44 and 47, respectively. The duration of thermal modification has a significant impact on color darkening. We also investigated the effect of different types of paints and varnishes applied to the surfaces of the samples subjected to heat treatment at different temperatures on the color state. A significant darkening of the end surface of the samples thermally modified at 160 °C and at 190 °C for 1 hour during the oil-wax and azure finishes was observed. That is, the color of wood obtained at a low processing temperature can be increased by applying these protective substances and make the material more attractive. The following studies evaluated the color stability of thermally modified wood additionally treated with oil-wax and azure, as well as the adhesion of these protective substances to the surface under the influence of environmental factors. The influence of different types of protective substances on the color of the surface of heat-treated wood was determined. The application of oil-wax and azure to the surface of the samples also affected the darkening of their color. It can be said that heat-treated samples, whose structure has changed compared to conventional wood, show different interactions with the applied materials.